Non-covalent interactions in supported asymmetric catalysis: a brief account - Ibos, Léa; Schulz, Emmanuelle (Comptes Rendus. Chimie)
Recent developments in asymmetric catalysis involve the heterogeneization of chiral complexes so that they can be easily immobilized on different supports. This account focuses on procedures that lead to the formation of non-covalent interactions between the chiral active sites and the chosen support, as they generally involve less tedious synthetic modifications and can allow either the chiral catalyst or the support to be easily recovered, at will. As a result, electrostatic interactions between inorganic supports and chiral organometallic complexes have been described to lead to efficient and recoverable catalysts. More recently, other weak interactions, such as ${π }$-interactions, but also donor–acceptor complexes, have been implicated for implementation of robust immobilizing procedures. There are also many examples of the use of coordination links, such as those present in metal organic frameworks for supported asymmetric catalysis, which pave the way for efficient cooperative or tandem asymmetric catalysis.